2019
DOI: 10.1371/journal.pone.0204195
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of bacterial and fungal communities during the infection of Brassica rapa roots by the protist Plasmodiophora brassicae

Abstract: The temporal dynamics of rhizosphere and root microbiota composition was compared between healthy and infected Chinese cabbage plants by the pathogen Plasmodiophora brassicae . When inoculated with P . brassicae , disease was measured at five sampling dates from early root hair infection to late gall development. The first symptoms of clubroot disease appeared 14 days after inoculation (DAI) and increased drastically between 14 and 35 DAI. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 74 publications
8
45
0
Order By: Relevance
“…The obtained results were consistent with those verified by Lebreton et al. (2019) when studying the rhizospheric composition dynamics of healthy and P. brassicae ‐infected Chinese cabbage plants. The authors reported a greater abundance of Proteobacteria, Firmicutes, Actinobacteria and Bacteroidetes in the rhizosphere of healthy plants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained results were consistent with those verified by Lebreton et al. (2019) when studying the rhizospheric composition dynamics of healthy and P. brassicae ‐infected Chinese cabbage plants. The authors reported a greater abundance of Proteobacteria, Firmicutes, Actinobacteria and Bacteroidetes in the rhizosphere of healthy plants.…”
Section: Discussionsupporting
confidence: 92%
“…Protists of free living can affect the populations of microorganisms in the soil and modify the rhizospheric microbiome through predation (by Bacteria, Archaea, Fungi and Algae) (Flues, Bass, & Bonkowski, 2017; Geisen & Bonkowski, 2017; Geisen et al., 2018; Hunninghaus, Koller, & Kramer, 2017; Jousset, 2017). Also, infection of chinese cabbage plants by P. brassicae can affect the temporal dynamics of its rhizosphere and its root microbiota composition (Lebreton et al., 2019). Pathogen growth and subsequent plant infection may be reduced due to positive plant interactions and microbial rhizosphere communities, which may have beneficial effects on plant growth and health, including the suppression of disease (Huang et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of L. maculans on the microbiome of oilseed rape residues was characterised with two near-isogenic oilseed rape lines, Darmor and Darmor-Rlm11, which carries an efficient resistance gene against stem canker. Oilseed rape residues with and without L. maculans infection are difficult to obtain in controlled conditions, by contrast to other pathosystems, such as Z. tritici on wheat residues (Kerdraon et al, 2019b) or Plasmodiophora brassicae on B. napus (Lebreton et al, 2019). There is also, generally, a large difference between the microbial communities present on plants in field conditions and those obtained in greenhouses (Ritpitakphong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the microbiota in the plant's response to a disease or in the pathogenicity of a fungal pathogen is currently being studied in various pathosystems, but remains poorly understood. Changes in microbial communities induced by the presence of plant pathogens and temporal changes in assemblies during the course of an epidemic are increasingly being studied with high-throughput sequencing techniques (Cho and Blaser, 2012;Jakuschkin et al, 2016;Lebreton et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…So, Mgnify ID MGYS00001376 refers to the still unpublished study of the infection of pedunculate oak by Erysiphe alphitoides, the causal agent of oak powdery mildew. And Mgnify ID MGYS00002393 applies to the temporal dynamics of bacterial and fungal communities during the infection of Brassica rapa roots by the protist Plasmodiophora brassicae [10]. Some recent works [11] focus on the characterization of fungal metagenomics in animal species, especially those from pig and mouse microbiomes.…”
Section: Introductionmentioning
confidence: 99%